2007
DOI: 10.1158/0008-5472.can-07-1805
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Vacuolar H+-ATPases as a New Strategy against Cancer

Abstract: Growing evidence suggests a key role of tumor acidic microenvironment in cancer development, progression, and metastasis. As a consequence, the need for compounds that specifically target the mechanism(s) responsible for the low pH of tumors is increasing. Among the key regulators of the tumor acidic microenvironment, vacuolar H + -ATPases (V-ATPases) play an important role. These proteins cover a number of functions in a variety of normal as well as tumor cells, in which they pump ions across the membranes. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
259
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 244 publications
(263 citation statements)
references
References 26 publications
(42 reference statements)
4
259
0
Order By: Relevance
“…Many recent studies have revealed that 1) cancer cells produce numerous protons (H + ) by active glycolysis under hypoxia, or the Warburg effect [39][40]; 2) the protons are stored in lysosomes and other acidic vesicles by vacuolar-type H + -ATPase (V-ATPase), resulting in the lysosomes and other acidic vesicles becoming even more acidic in the cancer cells than in normal cells [41][42]; 3) the extracellular fluid around cancer cells is also more acidic due to the larger number of protons excluded from the cytosolic space by NHE (Na-H + exchanger), V-ATPase and MCT (monocarboxylate transporter) than that of normal cells, or the larger number of protons produced by carbonic anhydrase 9 [43]. Since AO accumulates in acidic environments, sarcoma cells with a large number of acidic vesicles, are not able to exclude AO easily, whereas normal cells with non-acidic environments and weak acidic lysosomes can quickly exclude AO.…”
Section: Mechanism Of Selective Ao Accumulation In Sarcomasmentioning
confidence: 99%
“…Many recent studies have revealed that 1) cancer cells produce numerous protons (H + ) by active glycolysis under hypoxia, or the Warburg effect [39][40]; 2) the protons are stored in lysosomes and other acidic vesicles by vacuolar-type H + -ATPase (V-ATPase), resulting in the lysosomes and other acidic vesicles becoming even more acidic in the cancer cells than in normal cells [41][42]; 3) the extracellular fluid around cancer cells is also more acidic due to the larger number of protons excluded from the cytosolic space by NHE (Na-H + exchanger), V-ATPase and MCT (monocarboxylate transporter) than that of normal cells, or the larger number of protons produced by carbonic anhydrase 9 [43]. Since AO accumulates in acidic environments, sarcoma cells with a large number of acidic vesicles, are not able to exclude AO easily, whereas normal cells with non-acidic environments and weak acidic lysosomes can quickly exclude AO.…”
Section: Mechanism Of Selective Ao Accumulation In Sarcomasmentioning
confidence: 99%
“…It is conceivable that the tumor microenvironment conditions, including low pH (Fais et al , 2007 ;Fais , 2010 ), may be at least in part responsible for the increased exosome production and spillover in the bloodstream. These data make exosome detection in the human body fluids as one of the most important future clinical approach in the screening, diagnosis, and follow-up of tumor patients.…”
Section: Exosome-mediated Paracrine Propagation Within Tissues and Comentioning
confidence: 99%
“…Such signaling is proposed to contribute to the action of acidification on neoplastic 10 transformation and tumor aggressiveness, where acidification is brought about by key transporters, such as the Vacuolar (H+)-ATPase. (63) A localized cell surface pH gradient has also been implicated in cancer cell migration. (3,64,65) Cell migration can be linked to acidification through cancer cell tolerance, initiation of matrix breakdown and neighboring cell death (65) .…”
Section: Ph In Vivomentioning
confidence: 99%